Hypofractionated radiotherapy combined with targeted therapy or immunotherapy: Dutch survey on current practice, knowledge and challenges. (March 2022) - van Aken, Evert S.M.; van der Linden, Yvette M.; van Thienen, Johannes V.; de Langen, Adrianus J.; Marijnen, Corrie A.M.; de Jong, Monique C.; ,
Highlights: Radiotherapy referral during targeted therapy or immunotherapy occurs regularly. There is a knowledge gap regarding the implications of combined therapy. There is no consensus on expected toxicity of combined therapy. Multidisciplinary protocols regarding combined therapy are often not available. The application of radiotherapy treatment adaptations varies widely when combined with different systemic treatments. Abstract: Introduction: With the introduction of tyrosine kinase inhibitors and systemic antibodies, including immune checkpoint inhibitors, the survival of advanced-stage cancer patients has improved for many tumor types. These patients are increasingly referred for radiotherapy, but it is unclear whether radiotherapy combined with these drugs is safe. No international guidelines exist on whether or how to combine these drugs with radiotherapy. Therefore, we investigated the current clinical practice in the Netherlands regarding hypofractionated radiotherapy in patients using targeted drugs and immunotherapy. Materials and methods: We sent a survey to all 21 Dutch radiotherapy institutes. Dedicated radiation oncologists, medical oncologists and pulmonologists were asked to fill out the survey. The questions explored their familiarity with the combination of targeted drugs and immunotherapy with radiotherapy, the encountered clinical difficulties and factors influencing treatment decisions. Results: The survey was filled out by 54 respondents from 19 different institutes. The median annual number of patients per radiation oncologist referred for radiotherapy when using targeted drugs or immunotherapy was 10 and 15, respectively. Despite this high number, only 11% of the radiation oncologists stated that they had sufficient information (resources) for adequate treatment decision making. Among all physicians, 44% stated that there was insufficient knowledge within their institute regarding this topic. Only 17% stated that there was a multidisciplinary protocol available. The application of radiotherapy treatment adaptations (technique, dose, fractionation, field size) varied widely. Generally, there seemed to be no consensus regarding the expected toxicity of combined drug-radiotherapy treatments and the expected risk of tumor flare upon temporary drug discontinuation. Conclusion: There is no consensus amongst involved medical specialties on expected toxicity. Consequently, it is necessary to perform clinical studies examining the safety of combined drug-radiotherapy treatments, to add radiotherapy to phase I-III clinical trials for new drugs and to incorporate outcomes into multidisciplinary, evidence-based guidelines.